Analytical review of diagnosis and treatment strategies for dominant bile duct strictures in patients with primary sclerosing cholangitis - Aljiffry, Murad; Renfrew, Paul D.; Walsh, Mark J.; Laryea, Marie; Molinari, Michele (HPB (Oxford, England), 2011)
The diagnosis and treatment of indeterminate dominant strictures (DS) in patients with primary sclerosing cholangitis (PSC) is challenging and the literature on the subject is scarce. This review aims to appraise and synthesize the evidence published in the English-language medical literature on this topic. Scientific papers published from 1950 until week 4 of July 2010 were extracted from MEDLINE, Ovid Medline In-Process, the Cochrane Database of Systematic Reviews, the Database of Systematic Reviews, the Database of Abstracts of Reviews of Effects, EMBASE, PubMed and the National Library of Medicine Gateway. Strategies for the optimal management of DS in PSC patients are supported only by level II and III evidence. Intraductal endoscopic ultrasound appears to be the most sensitive (64%) and specific (95%) diagnostic test for the evaluation of DS in PSC. Endoscopic and percutaneous dilatations achieve 1- and 3-year palliation in 80% and 60% of patients, respectively. Although dilatation and stenting are the most common palliative interventions in DS, no randomized trials on the optimal duration of treatment have been conducted. In benign DS, endoscopic dilatation with short-term stenting seems to be effective and safe and does not increase the risks for malignant transformation or complications after liver transplantation. Surgical bile duct resection and/or bilioenteric bypass are indicated only in patients with preserved liver function.